Assessment and seasonal variations of communicable diseases: 3 year study - Kalyani, D.; Shankar, K. (International Journal of Research in Medical Sciences, 2016)
Background: Communicable diseases remain the leading cause of mortality and morbidity in developing countries as the disease patterns change constantly due to seasonal variation. The mechanisms responsible for the epidemiological consequences of this seasonal variation are poorly understood. Analysis of proper data of communicable diseases is required to determine the current burden as well as seasonality. The objectives of this study are to assess the current burden of various communicable diseases at Sir Ronald Ross Institute of Tropical and Communicable diseases (SRRIT&CD), to know the seasonal variations and to suggest preventive and curative measures. Methods: All patients who were admitted at this hospital over a period of three years (January 2011 to December 2013) have been studied. The patient data was documented for each case and further categorized into viral fevers, acute diarrheal diseases, enteric fever, malaria, rabies, measles, mumps, chickenpox, diphtheria, food poisoning, tetanus and pertussis. The incidence and seasonal variations for these diseases were analyzed. Results: Results showed that a total of 34,981 had been treated at the inpatient departments from the year 2011 to 2013. It was observed that communicable diseases constituted about 85% (30,082) of the total disease burden with viral infections being the commonest. Most of the diseases were observed to have a seasonal variation. The most common disease identified was viral fever 8713 (28.96%), secondly acute diarrheal diseases 7965(26.52%) followed by enteric fever 2958 (9.83%) and malaria 2443(8.12%). The least common were Rabies 80 (0.26 %) and pertussis 37 (0.12%). Outbreaks of Measles and Diphtheria were also noted in this study. Conclusions: Many diseases have a seasonal variation and the burden of these diseases could be reduced if we device measures to detect the changes in their trend through the implementation of surveillance programs. The knowledge of the burden of these would also assist the health administrators in allocation of the resources.